Decarboxylative cascade cyclization of α-keto acids with 2-cyano-3-arylaniline-derived acrylamides. Issue 43 (22nd October 2019) - Shang, Jia-Qi; Wang, Xiang-Xiang; Xin, Yangchun; Li, Yi; Zhou, Bin; Li, Ya-Min
Abstract : An oxidative decarboxylative cascade cyclization of α-keto acids with 2-cyano-3-arylaniline-derived acrylamides delivering carbonyl-containing pyrido[4, 3, 2- gh ]phenanthridines is presented. Abstract : An oxidative decarboxylative cascade cyclization of α-keto acids with 2-cyano-3-arylaniline-derived acrylamides was developed. This cascade reaction exhibits a broad substrate scope, and provides an efficient access to carbonyl-containing pyrido[4, 3, 2- gh ]phenanthridines. A possible mechanism is proposed.